Enthesitis-related arthritis and spondylarthritis: the same disease or disparate entities?. (2nd January 2022) - Ferjani Hanene, Lassoued; Ben Ammar, Lobna; Maatallah, Kaouther; Ben Nessib, Dorra; Triki, Wafa; Kaffel, Dhia; Hamdi, Wafa
ABSTRACT: Objectives: The aim of this study is to compare the clinical features, disease activity and physical impairment, between enthesitis-related arthritis, adult and late-onset spondylarthritis in Tunisian patients. Methods: This study included 190 patients divided into three groups according to their age at the onset of symptoms: ERA (onset of symptoms ≤ 16 years of age), AOSpA (16 < onset of symptoms < 50 years of age) and LOSpA (onset of symptoms ≥ 50 years of age). AOSpA and LOSpA patients fulfilled the ASAS criteria for SpA. Whereas, ERA patients were classified according to the ILAR criteria. Results: Among 190 patients, 21% had ERA, 70.5% had AOSpA, and 8.5% had LOSpA. There were no differences in gender ratio between ERA and AOSpA groups. Regarding the clinical presentation, ERA and LOSpA groups had more peripheral symptoms than AOSpA in whom the axial manifestation pattern continued throughout the course of the disease. HLA-B27 was more associated with ERA (p = 0, 007). Extra-articular manifestations were more observed in the ERA group (p = 0.004). Disease activity, functional status and anthropometric parameters were similar between groups. Nevertheless, health-related quality-of-life assessed by ASQoL and SF-36 scores were better in the AOSpA group but with no significant differences. Regarding the treatment option, methotrexate was widely used in the ERA group (p < 0.001). Conclusion: ERA is characterized mainly by marked peripheral arthritis, more extra-articular manifestations, and a higher frequency of hip involvement.